TEACHER IN SYSTEM DESIGN PAYROLL PLAYGROUP - Wiwit Hindrayani; Irfan Irfan, Skom, MM (Jurnal Sistem Informasi, 2002)
Computer technology is growing very fast, with this development has been a lot ofcompanies that menggunaka a computerized system in data processing employees.Computerized system is very helpful way of working a playgroup in data processingteacher salaries when compared with manual method.For this research writing that the author inging playgroup providing input on what theproblem so far is to convert the manual system to computerized system.Given this input the writer hopes this way the teacher payroll will be more quicklyand efficiently.